Copts in Modernity : Proceedings of the 5th International Symposium of Coptic Studies, Melbourne, 13-16 July 2018 - Agaiby, Elizabeth; Doorn-Harder, Nelly van; Swanson, Mark N. (Texts and Studies in Eastern Christianity, 2021)
"Copts in Modernity presents a collection of essays - many of which contain unpublished archival material - showcasing historical and contemporary aspects pertaining to the Coptic Orthodox Church. The volume covers three main themes: The first theme, History, gathers studies that look back to the nineteenth and late eighteenth centuries to understand the realities of the twentieth and twenty-first; the second theme, Education, Leadership and Service, explores the role of religious education in the revival of the Church and how Coptic religious principles influenced the ideas of leadership and service that resulted in the Church's spiritual revival; and the third theme, Identity and Material Culture, draws upon a broad range of material and visual culture to exemplify the role they play in creating and recreating identities. This volume brings together the work of senior and early career scholars from Australia, Europe, Egypt, and the United States"--